MEMBANGUN BRANDING MELALUI KOMUNIKASI DIGITAL - Saipul, Saipul; Rahmawati, Umi; Widyastuti, Widyastuti; Elisabeth, Christine Riani; Haryanto, Rudy (JURNAL LENTERA BISNIS, 2025)
The purpose of this study is to determine the effectiveness of building branding through digital communication. This research approach collects data through literature studies, which involve reading literature from various sources including reports, books, articles, and journals using qualitative and deductive approaches. The results of this study are that building branding through digital communication is not just following trends, but a strategic need in facing the dynamics of the modern market. Digital communication allows brands to reach a wider audience, establish more personal relationships, and manage brand image efficiently and measurably. With the right strategies such as building a strong digital identity, optimizing social media, providing quality content, optimizing websites and SEO, email marketing, and collaborating with influencers can form strong branding